The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.29252/shenakht.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spiritual health level and its related factors in the students of Sanandaj Universities, 2015

Abstract: Introduction: Spirituality is the most important aspect of human existentialism. This dimension is considered as a strong force in the center of life for more than one-third of the people worldwide. Spirituality is linked to health, a sense of goodness and recovery, and a factor in the continuation of life, finding its meaning and purpose. Aim: This study aimed to determine spiritual health level and its related factors in the students of Sanandaj universities in 2015. Method: The present study was a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on the findings of the present study, male nurses’ means of spiritual growth was at a good level and related to their BMI. Along with this, based on the findings of a study by Sayyadi et al, nurses’ spiritual health was reported to be medium and was related to their self-sufficiency ( Sayyadi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…Based on the findings of the present study, male nurses’ means of spiritual growth was at a good level and related to their BMI. Along with this, based on the findings of a study by Sayyadi et al, nurses’ spiritual health was reported to be medium and was related to their self-sufficiency ( Sayyadi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%